Asymmetric adult-onset asthma with periocular xanthogranuloma (AAPOX) associated with IgG4-related disease: a case report - Huang, Qiaomei; Chen, Zijian (Frontiers in Surgery, 2026)
BackgroundAdult orbital xanthogranulomatous disease is a rare non-Langerhans cell histiocytosis, among which the adult-onset asthma with periocular xanthogranuloma (AAPOX) subtype is particularly uncommon. Recent studies have suggested an association between this condition and IgG4-related disease (IgG4-RD), possibly falling within its disease spectrum.Case presentationA 60-year-old male presented with a one-year history of bilateral eyelid swelling accompanied by difficulty in opening the right eye. Examination revealed significant swelling and bulging of the right upper eyelid, with a well-defined, cord-like mass palpable on palpation. The left eyelid showed mild swelling without a detectable mass. The patient had a documented history of asthma, a positive bronchial provocation test, and significantly elevated serum IgE levels. Surgical intervention was performed on the right eye, followed by postoperative glucocorticoid therapy. Histopathological findings were consistent with xanthogranuloma, and IgG4 positivity suggested an association with IgG4-related disease (IgG4-RD). Serum IgG4 levels further supported this association. After treatment, the patient's serum IgG4 levels normalized, eyelid morphology improved significantly, and no progression was observed during a two-year follow-up period.ConclusionThis case further confirms the strong association between AAPOX and IgG4-RD, and represents the first report of asymmetric AAPOX. Surgical excision combined with systemic glucocorticoid therapy proved effective for this condition. Furthermore, the article explores the potential role of IgG4 produced during asthma desensitization therapy in the pathogenesis of IgG4-RD, suggesting that this potential risk should be considered during asthma treatment. This report provides valuable clinical experience for the diagnosis and treatment of such rare diseases.